2008
DOI: 10.1126/science.1156232
|View full text |Cite
|
Sign up to set email alerts
|

White Fat Progenitor Cells Reside in the Adipose Vasculature

Abstract: White adipose (fat) tissues regulate metabolism, reproduction, and life span. Adipocytes form throughout life, with the most marked expansion of the lineage occurring during the postnatal period. Adipocytes develop in coordination with the vasculature, but the identity and location of white adipocyte progenitor cells in vivo are unknown. We used genetically marked mice to isolate proliferating and renewing adipogenic progenitors. We found that most adipocytes descend from a pool of these proliferating progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
995
4
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 994 publications
(1,078 citation statements)
references
References 28 publications
54
995
4
14
Order By: Relevance
“…With regards to adipogenesis, Uezumi et al showed that PDGFRα+ MSCs, completely distinct from PDGFRβ+ pericytes, are responsible for adipogenesis in skeletal muscles and a balance between satellite cell-derived myofibres and PDGFRα+ cells maintain muscle homeostasis (Uezumi et al, 2010). However, differentiation of pericytes into adipocytes has been documented (Birbrair et al, 2013a;Farrington-Rock et al, 2004;Tang et al, 2008), and the differences between studies may well be dependent on the muscle condition and the subsequent interaction between cell types in the context of muscle injury.…”
Section: Muscle Injurymentioning
confidence: 99%
“…With regards to adipogenesis, Uezumi et al showed that PDGFRα+ MSCs, completely distinct from PDGFRβ+ pericytes, are responsible for adipogenesis in skeletal muscles and a balance between satellite cell-derived myofibres and PDGFRα+ cells maintain muscle homeostasis (Uezumi et al, 2010). However, differentiation of pericytes into adipocytes has been documented (Birbrair et al, 2013a;Farrington-Rock et al, 2004;Tang et al, 2008), and the differences between studies may well be dependent on the muscle condition and the subsequent interaction between cell types in the context of muscle injury.…”
Section: Muscle Injurymentioning
confidence: 99%
“…Recent evidence suggests that white adipocytes may have different origins along the anterior-posterior axis: neural crest in the cephalic region, and putatively mesoderm in the trunk (Billon et al, 2008). In addition, at least some precursors of white fat cells may derive from mural cells associated with blood vessels in mice (Tang et al, 2008).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
“…Indeed, it has long been known that a large pool of preadipocytes exists in human adipose tissue (Fischer-Posovszky et al, 2007). The finding of a pool of early committed white adipocyte precursors in the mural cell compartment of the adipose vasculature supplies an additional putative source for new adipocytes (Tang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%